Urbanisation et viabilité de l'activité maraîchère : cas d'une ville à statut particulier au Bénin (Parakou) - Guy Nouatin; François-Xavier Bachabi (VertigO)
The cities of developing countries are in complete mutation. This mutation is characterized by an increase of their population and urbanization. These two factors submit them to two major challenges. The first concerns how the populations can get supplies of trucks and the second is relative to the land problem to which urban market gardeners face. This paper studies the land pressure the urban market gardeners are confronted with. Parakou, the third Benin City with particular status, undertook these last years, an urbanization policy in order to find accommodations for the residents and to install adequate infrastructures for its development. The urbanization led to the occupation of the lands used for the market gardening for other purposes, putting the market gardeners in land insecurity. The objective of the study is to analyze the impacts of the urbanization of Parakou City on the market gardening. We used a qualitative methodology based on an inventory of market gardening sites in the city and on interviews with the actors concerned by this activity. One out of the seven recorded sites is under closure. None of them gave a guarantee to the market gardeners for undertaking sustainable investment because they don't have any secured property title. It appears also that, nothing is made to facilitate the development of market production that assures people food security in Parakou.